GEOCHEMICAL SPECIALISATION OF ROCKS OF THE ALKALINE BASALTOID-LAMPROPHYRE FORMATION OF THE CHAKYLKALYAN MOUNTAINS - Yarboboev, Tulkin; Sultonov, Shukhrat (Innovatsion texnologiyalar, 2023)
This paper is devoted to the results of studies and analyses to determine the geochemical specialisation of rocks of the alkaline basaltoid-lamprophyre formation of the Chakilkalyan Mountains. The results of studies show that the rocks of the alkaline basaltoid-lamprophyre formation of the eastern part of the Chakylkalyan-Karatyubinsk mining and ore district belong to the same genetic diatreme-dyke complex of regional distribution, forming dyke belts and areas in different areas of the Southern and Middle Tien Shan. The xenoliths of verlites, olivine pyroxenites, harzburgites and lherzolites detected in the rocks of the alkaline basaltoid-lamprophyre formation characterise the fluidised and metasomatised upper mantle. Dyke rocks of the intraplate stage of all studied areas are characterised by geochemical specialisation for gold and rare-metal mineralisation.